Punitive damages for oil spills: a look from the economic analysis of law - Bolaños Rodríguez, Miguel Ángel (2022)
Given the difficulties of making an adequate compensation for environmental damage caused by oil spills, this article presents the treatment of Law of Torts and summarizes the American experience in the case of environmental damage caused by oil spills through punitive damages. Likewise, through an Economic Analysis of Law, the evaluation of the efficiency of punitive damages in terms of compensation for environmental damage due to oil spills is presented and compared to administrative sanctions for environmental damage.